2020
DOI: 10.1101/2020.03.07.20032516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting heterogeneity of intervention effects using analysis and meta-analysis of differences in variance between arms of a trial

Abstract: Randomised controlled trials (RCTs) with continuous outcomes usually only examine mean differences in response between trial arms. If the intervention has heterogeneous effects (e.g. the effect of the intervention differs by individual characteristics), then outcome variances will also differ between arms. However, power of an individual trial to assess heterogeneity is lower than the power to detect the same size of main effect. The aim of this work was to describe and implement methods for examining heteroge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 51 publications
(83 reference statements)
0
25
0
Order By: Relevance
“…Different requirements and assumptions apply to the VR and the CVR. Both assume normality of the data, although for the CVR, adjustments to the calculation can make the method suitable for non-normally distributed data [48]. The CVR, additionally, requires the data to be measured on a ratio scale [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different requirements and assumptions apply to the VR and the CVR. Both assume normality of the data, although for the CVR, adjustments to the calculation can make the method suitable for non-normally distributed data [48]. The CVR, additionally, requires the data to be measured on a ratio scale [48].…”
Section: Discussionmentioning
confidence: 99%
“…Both assume normality of the data, although for the CVR, adjustments to the calculation can make the method suitable for non-normally distributed data [48]. The CVR, additionally, requires the data to be measured on a ratio scale [48]. However, given the psychometric properties of the HAMD and the MADRS, and likely other depression severity rating scales, they should not be considered ratio scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 By comparing the variances between treatment and control groups of RCTs, 11 greater variability in treatment would indicate that there is a component of variation, the side effect-by-patient or side effect-by-subgroup interaction, that indicates variability of side effects. 10 Note that this method 12 has recently been applied for antipsychotics, 6 antidepressants, 7,13,14 and brain stimulation. 15 It is worth noting that these studies found little evidence for treatment effect variation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,13,14 Importantly, in the case of pre-post differences used as input for a meta-analysis of variance it is crucial to think carefully about the way the variability ratio is expressed, 11,14,16 as the use of the coefficient of variation ratio (CVR) that has been proposed as an alternative of the variability ratio (VR) 11 may lead to unreliable results. 12,16…”
Section: Introductionmentioning
confidence: 99%